Determining Hair Thickness using the Light Diffraction Method: Verification of the Seven Times Sliced Hair Phenomenon - Ellianawati Ellianawati; Muhammad An’im Arravi; Fitria Wulandari; Rofita Istiqomah (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2018)
Light or optical spectrum is a part of electromagnetic radiation and has several electromagnetic wave properties; one of them is undergoing diffraction. Diffraction or light bending occurred when a light went through a narrow gap. By utilizing that principle, it was proven that a piece of hair could be assumed as a single gap, so the thickness of a piece of hair could be determined, which lead to the explanation of the phenomenon of a piece of hair sliced seven times. As a tool, the used sim cardholder is used to put hair using adhesive tape. Then the sim card is placed between the light source and the screen. The light source used is a red laser with a wavelength of 660 nm. Hair is placed in two positions: horizontally and vertically. Hair that is laid horizontally will create a vertical light-dark pattern, and hair that is placed vertically will form a horizontal light-dark pattern. The dark and light patterns on the screen are measured using a ruler according to the order of each pattern that is formed. The hair thickness measurement results using a red laser with a wavelength of 660 nm obtained hair thickness of d = (0.01146 ± 0.00019) cm for hair that is placed horizontally and d = (0.01151 ± 0.00011) cm for vertically placed hair. This data has more or less proven that there is potential to